A multi‐program analysis of cleft lip with cleft palate prevalence and mortality using data from 22 International Clearinghouse for Birth Defects Surveillance and Research programs, 1974–2014 - Mc Goldrick, Niall (2023)
Background:Cleft lip with cleft palate (CLP) is a congenital condition that affects both the oral cavity and the lips. This study estimated the prevalence and mortality of CLP using surveillance data collected from birth defect registries around the world.Methods:Data from 22 population- and hospital-based surveillance programs affiliated with the International Clearinghouse for Birth Defects Surveillance and Research (ICBDSR) in 18 countries on live births (LB), stillbirths (SB), and elective terminations of pregnancy for fetal anomaly (ETOPFA) for CLP from 1974 to 2014 were analyzed. Prevalence and survival (survival for LB only) estimates were calculated for total and subclassifications of CLP and by pregnancy outcome.Results:The pooled prevalence of total CLP cases was 6.4 CLP per 10,000 births. The prevalence of CLP and all of the pregnancy outcomes varied across programs. Higher ETOPFA rates were recorded in most European programs compared to programs in other continents. In programs reporting low ETOPFA rates or where there was no ascertainment of ETOPFA, the rate of CLP among LB and SB was higher compared to those where ETOPFA rates were ascertained. Overall survival for total CLP was 91%. For isolated CLP, the survival was 97.7%. CLP associated with multiple congenital anomalies had an overall survival of 77.1%, and for CLP associated with genetic/chromosomal syndromes, overall survival was 40.9%.Conclusions:Total CLP prevalence reported in this study is lower than estimates from prior studies, with variation by pregnancy outcomes between programs. Survival was lower when CLP was associated with other congenital anomalies or syndromes compared to isolated CLP.